VIRTUAL LEARNING ENVIRONMENTS AND SMART PAPERS IN LARGE-SCALE ASSESSMENTS - Baumgratz, Helen Cristina Minardi; dos Santos, Rodrigo Otávio (Seven Editora, 2024)
This article presents the results of the qualitative analysis of the literature on the use of Virtual Learning Environments and Smart Paper technology in large-scale evaluations in the Brazilian educational context. The research revealed that virtual learning environments offer tools to make assessments more efficient, although they face challenges such as the need for adequate infrastructure and equity in technological access. On the other hand, Smart Paper technology emerges as a promising solution to overcome access and cost obstacles, integrating digital resources into the paper format. It was concluded that these technologies can enrich evaluation practices and support more effective and inclusive educational policies. DOI:https://doi.org/10.56238/sevened2024.037-032